INOVASI PEMBELAJARAN PROJECT BASED LEARNING TEMATIF INTEGRATIF BAGI GURU-GURU SMA MUHAMMADIYAH 2 PONTIANAK - Yulian, Ryani; Ruhama’, Ufi; Insyira, Maulidya Raissa (Jurnal Abdi Insani, 2024)
Education is the foundation for shaping a quality and competitive generation. One of the main elements of the learning process is educational innovation, which can refine the quality of learning practices and actively engage students. One such innovation is project-based learning (PjBL). Therefore, this community service activity was organized to provide training for teachers at SMA Muhammadiyah 2 Pontianak in designing innovative learning methods. Through the implementation of PjBL, teachers are expected to develop students' critical thinking skills and prepare them to face real-world challenges. The objective of this community service activity is to conduct training for teachers to enhance their ability to develop integrative thematic project-based learning that focuses on critical thinking skills, thus creating enjoyable and meaningful learning experiences for students. The training methods include delivering material, demonstrations, and interactive discussions. The training is divided into three main sessions: theoretical presentations, practical demonstrations, and a dialogue and Q&A session to deepen participants' understanding of the material presented. The results of the activity showed an improvement in teachers' knowledge, especially through the interactive delivery of theory, demonstrations, and discussions. Teachers not only gained a deep understanding of the PjBL concept but also became more capable of designing and implementing projects in the classroom, despite challenges such as limited time and resources. The increase in the average score from 50 in the pretest to 80 in the posttest reflects an enhanced understanding, with teachers becoming more skilled in designing projects that meet students' needs. Additionally, the understanding of the fundamental differences between PjBL and problem-based learning (PBL) became clearer, with teachers now able to differentiate the focus of these two approaches. The training activity successfully improved teachers' understanding of project-based learning to support the development of 21st-century skills in students. Through the delivery of theory, demonstrations, and discussions, teachers were able to grasp strategies for implementing project-based learning, even with the constraints of time and resources.